2015
DOI: 10.1182/blood.v126.23.609.609
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Prognostic Markers and the Performance of Scoring Systems in 1837 Patients with Therapy-Related Myelodysplastic Syndrome - a Study of the International Working Group (IWG-PM) for Myelodysplastic Syndromes (MDS)

Abstract: Background: The International Prognostic Scoring System (IPSS) for MDS has recently been revised (IPSS-R). However both scoring systems were developed after exclusion of therapy-related cases and data on its usefulness in treatment-related MDS (tMDS) is limited. Aims and Methods: We analyzed 1837 pts from Spanish, German, Swiss, Austrian, US, Italian, and Dutch centers diagnosed 1975-2015. Complete data to calculate the IPSS/-R was available in 1511 pts. The impact of prognostic features was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…A large cooperative study investigated epidemiology and outcome of 1837 t-MDS patients. 8 Median age was 68 years and cytogenetic risk according to the revised International Prognostic Scoring System (IPSS-R) was 2% very good, 36% good, 17% intermediate, 15%…”
Section: Epidemiology Of Therapy-related Myeloid Neoplasms Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…A large cooperative study investigated epidemiology and outcome of 1837 t-MDS patients. 8 Median age was 68 years and cytogenetic risk according to the revised International Prognostic Scoring System (IPSS-R) was 2% very good, 36% good, 17% intermediate, 15%…”
Section: Epidemiology Of Therapy-related Myeloid Neoplasms Classificationmentioning
confidence: 99%
“…In the aforementioned large cooperative study of 1837 t-MDS patients, the median OS was 16 months, and allogeneic HCT was performed in 16% of patients who had a median survival of 24 months. 8 The discriminatory power of the IPSS-R was inferior in t-MDS compared with de novo MDS patients and a revised prognostic model was proposed. 8 Another study compared the IPSS-R score in t-MN patients to de novo MDS patients and found that the IPSS-R score can distinguish the 5 prognostic subgroups, but OS was shorter in t-MN patients than in de novo MDS patients, particularly in the very-low-risk and low-risk groups.…”
Section: Treatment-related Mdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Anamnese des Patienten muss gründlich erhoben werden, insbesondere in Bezug auf vorangegangene Behandlungen mit Chemotherapeutika, und/oder Radiotherapie oder Radiojodtherapie, da diese das Risiko der Entwicklung eines MDS begünstigen. Dies ist der Fall bei etwa 10 % der MDS-Patienten [5,6]. Eine berufliche Belastung mit organischen Lösungsmitteln, insbesondere Benzol über einen langen Zeitraum, erhöht ebenfalls das Risiko für die Entwicklung eines MDS [7].…”
Section: Diagnostikunclassified
“…8 The discriminatory power of the IPSS-R was inferior in t-MDS compared with de novo MDS patients and a revised prognostic model was proposed. 8 Another study compared the IPSS-R score in t-MN patients to de novo MDS patients and found that the IPSS-R score can distinguish the 5 prognostic subgroups, but OS was shorter in t-MN patients than in de novo MDS patients, particularly in the very-low-risk and low-risk groups. 56 The median survival in t-MDS patients with very-low-, low-, and intermediaterisk IPSS-R was 56.5, 21.7, and 15.8 months, respectively, whereas de novo MDS patients had median survival of 105.6, 63.6, and 36 months.…”
Section: Treatment-related Mdsmentioning
confidence: 99%